Redox regulation of surface protein thiols: Identification of integrin α-4 as a molecular target by using redox proteomics - Laragione, Teresa (National Academy of Sciences, 2003)
Thiols affect a variety of cell functions, an effect known as redox regulation. We show here that treatment (1–2 h) of cells with 0.1–5 mM N-acetyl-l-cysteine (NAC) increases surface protein thiol expression in human peripheral blood mononuclear cells. This effect is not associated with changes in cellular glutathione (GSH) and is also observed with a non-GSH precursor thiol N-acetyl-d-cysteine or with GSH itself, which is not cell-permeable, suggesting a direct reducing action. NAC did not augment protein SH in the cytosol, indicating that they are already maximally reduced under normal, nonstressed, conditions. By using labeling with a non permeable, biotinylated SH reagent followed by two-dimensional gel electrophoresis and analysis by MS, we identified some of the proteins associated with the membrane that are reduced by NAC. These proteins include the following: integrin α-4, myosin heavy chain (nonmuscle type A), myosin light-chain alkali (nonmuscle isoform), and β-actin. NAC pretreatment augmented integrin α-4-dependent fibronectin adhesion and aggregation of Jurkat cells without changing its expression by fluorescence-activated cell sorter, suggesting that reduction of surface disulfides can affect proteins function. We postulate that some of the activities of NAC or other thiol antioxidants may not only be due to free radical scavenging or increase of intracellular GSH and subsequent effects on transcription factors, but could modify the redox state of functional membrane proteins with exofacial SH critical for their activity.